Cysto-biliary communication (CBC) in hepatic hydatidosis: predictors, management and outcome - Dinakar Reddy, A.; Thota, Anuroop (International Surgery Journal, 2018)
Background: Liver hydatidosis is a common health problem in endemic areas. Cystobiliary communication is the most common complication of liver hydatid. Methods: Cases of liver hydatid operated during the period June 2012 to July 2018 were retrospectively assessed. Patients diagnosed with cystobiliary communication (preoperatively, intraoperatively or postoperatively) were analysed. Demographics, laboratory tests were noted. Computed tomographic (CT) findings including size, location, Gharbi’s type, presence of intrahepatic biliary radical dilatation, CHD and CBD dilatation were noted. Intraoperative findings were noted. Postoperative outcomes and any intervention if done were noted. Results were analysed. Results: Around 108 patients with liver hydatid underwent surgical intervention. Of which 20 (18.5%) patients were found to have cystobiliary communication. Mean cyst size was 8cms. Location of cyst in segment IV and V commonly. 8 patients were diagnosed preoperatively by elevated bilirubin and alkaline phosphatase and on contrast enhanced computerized tomography. Out of 8, 4 patients underwent preop ERCP and stenting, followed by surgery and the other 4 underwent direct surgery with CBD exploration. 4 were diagnosed intraoperatively and the fistula site sutured. But 2 patients had postop biliary fistula which required postop ERC and stenting. Remaining 8 presented postoperatively with biliary fistula. Of 8 patients, 2 had major and 6 had minor fistulas. Postoperative mortality was 0%. Conclusions: Cystobiliary communication is more common in males with large cyst size, located in the central segments of liver close to biliary confluence, Gharbi type IV cysts. Timely diagnosis and appropriate management decrease the morbidity and mortality.